Alveolar bone healing process in spontaneously hypertensive rats (SHR). A radiographic densitometry study - Manrique, Natalia [UNESP]; Pereira, Cassiano Costa Silva [UNESP]; Garcia, Lourdes Maria Gonzáles [UNESP]; Micaroni, Samuel [UNESP]; de Carvalho, Antonio Augusto Ferreira [UNESP]; Perri, Sílvia Helena Venturoli [UNESP]; Okamoto, Roberta [UNESP]; Sumida, Doris Hissako [UNESP]; Antoniali, Cristina [UNESP] (My University, 2012)
Hypertension is one of the most important public health problems worldwide. If undiagnosed or untreated, this pathology represents a systemic risk factor and offers unfavorable conditions for dental treatments, especially those requiring bone healing. Objectives: The purpose of this study was to demonstrate, by analysis of bone mineral density (BMD), that the alveolar bone healing process is altered in spontaneously hypertensive rats (SHRs). Material and Methods: Wistar rats and SHRs were submitted to extraction of the upper right incisor and were euthanized 7, 14, 21, 28 and 42 days after surgery. Right maxillae were collected, radiographed and analyzed using Digora software. BMD was expressed as minimum (min), middle (med) and maximum (max) in the medium (MT) and apical (AT) thirds of the dental alveolus. Results: The results were compared across days and groups. Wistar showed difference in med and max BMD in the MT between 7 and 28 and also between 14 and 28 days. The AT exhibited significant difference in med and min BMD between 7 and 28 days, as well as difference in min BMD between 28 and 42 days. SHRs showed lower med BMD in the MT at 28 days when compared to 21 and 42 days. Differences were observed across groups in med and min BMD at day 28 in the MT and AT; and in max BMD at 14, 21 and 42 days in the MT. Conclusions: These results suggest that the alveolar bone healing process is delayed in SHRs comparing with Wistar rats.
Keywords: Bone density; Hypertension; Spontaneously hypertensive rats; Tooth socket